A survey of ectoparasites on domestic cat (felis catus linnaeus, 1758) from rural and urban area - Nur Izzah Izzati, Binti Ahmad (Universiti Malaysia Sarawak (UNIMAS), 2013)
A survey of ectoparasites on domestic cats from two different habitats has been conducted in six different locations from October 2012 to March 2013. A total 69 of domestic cats have been examined for the presence of ectoparasites, comprising 34 from urban habitat and 35 from rural habitat. Thirty six (52.1%) domestic cats have been discovered to be infested with at least one species of ectoparasites. Eight species of ectoparasites manage to be collected throughout the study. Felicola subrostrata (21.7%) is the common ectoparasite recovered from the infested host. Listophorid mites (14.5%) show the high infestation on domestic cat from rural habitat. Sarcoptes scabiei (10.1%), Notoedes cati (8.7%), Ctenocephalides felis (7.2%) infested the both rural and urban domestic cat with the quite similar rate of infestation. Meanwhile, Heterodoxus spiniger (2.9%) and other two species of Ixodid tick, which both show 1.4% of infestation rate only found on the urban domestic cats. However, S. scabiei and C. felis are the only ectoparasites species among that have been found are important in medical point of view. There is significant different in species diversity (χ2 =38.29, p=0.00), as urban habitat show the higher number of ectoparasite species compared to the rural habitat.